The Determinants of CDS Bid-ask Spreads - Marcin Wojtowicz (Tinbergen Institute, 2014)
We investigate the determinants of bid-ask spreads on corporate credit default swaps (CDSs). We find that proxies for dealer inventory costs such as variability of CDS premia and CDS trading volume explain as much as 80% of variation in CDS bid-ask spreads. We also analyze the influence of variables capturing systematic risk of reference entities, market-implied volatility, dealer funding costs and competition between dealers. Several of these variables are significant, but their explanatory power is moderate. Finally, we demonstrate that CDS bid-ask spreads do not widen preceding earnings announcement surprises, which suggests that private information does not hinder CDS liquidity.
Keywords: G10; G14; G19; 330; Credit default swaps; Liquidity; Bid-ask spreads; Components of bid-ask spreads